Assesing Water Infiltration Potential to Suport Sustainable Community Development - Ariyani, Dwi; Arini, Resti Nur; Kirani, Fachriza Putri; Inggraini, Maulin; Anindita, Reza (Universitas Serang Raya, 2025)
The availability of clean water is a basic need often unmet in several areas of Indonesia, including Sukagalih Village in Jonggol District, Bogor Regency, West Java. The village faces difficulty accessing clean water due to population growth, climate change, and a lack of water management infrastructure. The community service initiative aims to help address these issues by identifying available water sources and mapping the potential recharge areas in Jonggol District. The methods used include primary data collection through field observations and interviews with the community, direct measurement of water discharge at the source using a flow meter to determine the flow rate at the water source, while the determination of the groundwater recharge area is based on four parameters: rainfall; slope; land use; and soil type. Based on the results of activities and analysis, four water sources are located in Dusun 2 and Dusun 3 with a discharge of 0.126 liters/second, which does not yet meet the community's raw water needs. Based on the analysis of the potential of the groundwater recharge area, Sukagalih village has a high potential for groundwater recharge areas based on rainfall data, soil, land use, and slope gradient.